Gemcitabine-loaded poly (lactide-co-glycolide) – poly (ethylene glycol) gold nanoparticles: Evaluating the effect of fabricating methods on physicochemical characteristics, in vitro drug release and cytotoxicity - Shakri, Adibah; Mohd Paad, Khairunnisa; Saad, Norazalina; Mohamed Suffian, Izzat Fahimuddin (Springer, 2025)
Hybrid gold nanoparticles (AuNPs) are defined as a combination of organic and inorganic materials used as nanocarriers in the drug delivery system to enhance the performance of the drugs. Methods to fabricate the hybrid AuNPs such as double emulsion and nanoprecipitation require several steps and are inconsistent in their physicochemical characteristics limiting their application in drug delivery. The electrospray method has become a powerful tool for fabricating nanoparticles due to its simplicity, rapidity and consistency. Hence, this study aims to evaluate the performance of hybrid AuNPs prepared by two different methods; double emulsion and electrospray including the physicochemical characteristics, drug release profile and in vitro cytotoxicity. Hybrid AuNPs were prepared using double emulsion and electrospray methods. Then, the formed particles' hydrodynamic size, polydispersity index (PDI) and zeta potential were characterised using a Zetasizer Nano ZS. Furthermore, the drug release kinetics and cytotoxicity effects were evaluated using the dialysis method and the MTT assay. Hybrid AuNPs formed by the electrospray method (HAES) exhibit smaller particle sizes at 147.00 ± 10.4 nm with a PDI value of 0.35 ± 0.01 and zeta potential of -31.5 ± 2.6 compared to hybrid AuNPs formed using double emulsion methods (HADE) which exhibit larger particle sizes of 287.47 ± 1.87 nm with PDI value of 0.25 ± 0.09 and zeta potential of -23.30 ± 0.6. This study suggests that HAES prevent burst effects during drug release due to polymer composition changes under different temperatures that can enhance the drug delivery system. From the MTT assay, at 50 mg mL−1, the HAES exert higher toxicity effects of 50% compared to HADE due to different physicochemical characteristics and drug release patterns. These findings emphasise the advantage of the electrospray method in fabricating polymeric gold hybrid nanoparticles by forming smaller particle sizes, stable formulation, and higher toxicity to cancer cells compared to particle synthesis by the double emulsion method.